Characterization of the complete mitochondrial genome of lesser grain borer Rhyzopertha dominica Fabricius (Insecta: Coleoptera: Bostrichidae) from Jingziguan - Bocheng Ouyang; Yu Bai; Jun Chen; Junyang Wang; Sheng Liang (Mitochondrial DNA. Part B. Resources, 2019)
The lesser grain borer, Rhyzopertha dominica (Fabricius) is a primary pest of starch-containing stored products worldwide. Here, we report characterization of mitogenome of R. dominica and its phylogenetic position. Rhyzopertha dominica complete mitochondrial genome (GenBank accession number MN527959) from Jingziguan town consisted of a circular DNA molecule of 15,862 bp (with 74.36% A + T content). The mitogenome comprised of 13 protein-coding genes (PCGs), and 22 tRNA and two rRNA genes. PCGs had typical ATN (Met) initiation codons and were terminated by typical TAN stop codons.